Demystifying infant vocal imitation: The roles of mouth looking and speaker's gaze. Issue 6 (12th April 2019) - Imafuku, Masahiro; Kanakogi, Yasuhiro; Butler, David; Myowa, Masako
Abstract: Vocal imitation plays a fundamental role in human language acquisition from infancy. Little is known, however, about how infants imitate other's sounds. We focused on three factors: (a) whether infants receive information from upright faces, (b) the infant's observation of the speaker's mouth and (c) the speaker directing their gaze towards the infant. We recorded the eye movements of 6‐month‐olds who participated in experiments watching videos of a speaker producing vowel sounds. We found that an infants' tendency to vocally imitate such videos increased as a function of (a) seeing upright rather than inverted faces, (b) their increased looking towards the speaker's mouth and (c) whether the speaker directed their gaze towards, rather than away from infants. These latter findings are consistent with theories of motor resonance and natural pedagogy respectively. New light has been shed on the cues and underlying mechanisms linking infant speech perception and production. Abstract : We explored infant's ability to vocally imitate. We found that infants produced more vocal imitation when looking at (i) upright (rather than inverted) faces, (ii) the mouth (rather than eyes) of the speaker, and (iii) when the speaker was looking directly at (rather than away from) the infant. These findings shed new light on the cues and underlying mechanisms linking infant speech perception and production.